Forest aboveground biomass accumulation lags forest canopy recovery in degraded tropical forests of Ghana - Dan Wanyama; Michael C. Wimberly; Russell Doughty; Foster Mensah (International Journal of Applied Earth Observations and Geoinformation)
Long-term records from optical remote sensing are commonly used to monitor forest change but have limited capacity to measure the vertical distribution of tree canopy. This study integrated spaceborne Global Ecosystem Dynamics Investigation (GEDI) Lidar data with disturbance histories from Landsat time series and active fire detections from VIIRS and MODIS to assess changes in aboveground biomass density (AGBD) associated with fire and non-fire disturbance and forest canopy recovery. The study was conducted in four tropical forest zones in Ghana. We summarized changes and patterns of forest disturbances and their effects on AGBD. We then generated smoothed time series graphs of AGBD against time since the last event (forest loss, degradation, or canopy recovery) and compared them to AGBD in undisturbed forests in each zone. The results showed that biomass accumulation in tropical forests of Ghana was associated with their disturbance and recovery histories. Locations that experienced forest loss in the past had the lowest amounts of biomass and average biomass steadily increased along a continuum from loss to degradation to recovery to undisturbed across all four forest zones. Forest biomass did not increase within the first 16 years following the last degradation event. This suggests that degraded forests might be facing ongoing low-severity disturbances, which lead to further tree mortality and hinder regeneration and growth. Biomass was lower than in undisturbed forests even after canopy recovery was detected with Landsat, taking 5–16 years to reach pre-disturbance levels in the various zones. Our study demonstrates the utility of integrating optical remote sensing data with GEDI Lidar data to monitor these changes more comprehensively. Such information can aid in planning the sustainable use and effective rehabilitation of tropical forests in Ghana and similar tropical regions.